Evaluation of the efficiency of gray water treatment using Moringa oil seeds under different test methodologies (Research, Society and Development, 2020)
The growing demand for water and the growing occurrence of water scarcity events result in the need for more sustainable practices in water management and treatment. Therefore, the search for efficient techniques for the treatment of effluents followed by its reuse, has gained prominence today. One of the options for treating effluents in a decentralized and efficient way is the use of natural coagulants based on the oil Moringa seed (MO). In this context, the present work experimentally evaluates the efficiency of the treatment of waste water from the washing machine using coagulants based on MO seed, in order to promote the reuse of this effluent. For that, coagulation tests were performed in Jar Test considering the use of OM seed both directly (crushed) and also in saline solution. The efficiency of clarification and removal of COD from the crude sample were evaluated for several scenarios of initial turbidity and volume of coagulant. The results obtained showed that both in direct use and in saline solution were inefficient, being necessary the optimization of the dosage of the used coagulant or a new methodology of extraction of the coagulant. Broader discussions of the potentials and limitations of the use of OM could be constructed based on the results obtained.